Cabaran utama pemilikan rumah mampu milik bagi golongan berpendapatan sederhana - Zainal Abidin, Eniza (2021)
Homeownership is a very important property in providing space and comfort as well as a place of refuge in ensuring the safety of individuals and families. However, as stated in real estate reports, the news, in the press shows that rising house prices are increasing day by day it has put pressure on those who do not yet own their own homes, especially those who work and live in major cities in Malaysia. The house prices offered in urban areas are very expensive compared to the suburbs. This makes it difficult for middle-income people to own their own home. Therefore, this study aims to examine the main challenges of affordable housing ownership for the middle-income group (M40). A total of 100 questionnaires were distributed to civil servants serving in Johor Bahru City. The results of the study found that the main challenges are the increasing daily expenses and the location of the desired or desirable home of high value. In addition, the increase in total expenditure, high house market price, 5% full loan interest rate is too high, difficulty in paying other fees, changes in other matters and having various other loans among other major challenges affecting home ownership affordable among M40. These findings should be given attention and refined by policy makers in an effort to formulate and improve the implementation of national housing policy and development so that all groups can own a house and achieve the main objectives of the national housing policy.